Some types of Sepsidae in the Berlin and Eberswalde Museums (Diptera). - Ozerov, Andrej Leonidovitsch (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Fourty three primary types of Sepsidae in the Zoological Museum, Museum für Naturkunde an der Humboldt-Universität zu Berlin, and in the collections of the Deutsches Entomologisches Institut, Eberswalde, are treated. Lectotypes are designated for 26 species, 3 new junior synonyms are reported, and 3 names are re-instated. Nomenclatural Actslaticornis (Duda, 1926) (Archisepsis), Lectotype described as Sepsis laticornisniveipennis (Becker, 1903) (Australosepsis), Lectotype described as Sepsis niveipenniscrassiseta Duda, 1926 (Enicita annulipes var.), Lectotype now a synonym of Themira annulipes (Meigen, 1826)simplicicrus Duda, 1926 (Leptomerosepsis), Lectotypepectinulata Loew, 1873 (Nemopoda), Lectotypedentatiformis (Duda, 1926) (Palaeosepsis), Lectotype described as Sepsis dentatiformismaculata (Duda, 1926) (Palaeosepsis), Lectotype described as Sepsis dentata var. maculatanigritarsis Duda, 1926 (Paratoxopoda), Lectotype now a synonym of Paratoxopoda tricolor (Walker, 1849)flavitarsis Duda, 1926 (Paratoxopoda nigritarsis var.), Lectotype now Paratoxopoda flavitarsisspeiseri Duda, 1926 (Pseudonemopoda), Lectotypealbolimbata Meijere, 1913 (Sepsis), Lectotype now a synonym of Sepsis dissimilis Brunetti, 1910arotrolabis Duda, 1926 (Sepsis), Lectotypecoprophila Meijere, 1906 (Sepsis), Lectotypefemoriseta Duda, 1926 (Sepsis), Lectotypefissa Becker, 1903 (Sepsis), Lectotypeglabra Duda, 1926 (Sepsis), Lectotype now a synonym of Sepsis igniventris Thomson, 1869hirtipes Becker, 1903 (Sepsis), Lectotype now a synonym of Lasiosepsis melanota (Bigot, 1886)latiforceps Duda, 1926 (Sepsis), Lectotypemacrochaetophora Duda, 1926 (Sepsis), Lectotypemelanopoda Duda, 1926 (Sepsis), Lectotype now a synonym of Sepsis flavimana Meigen, 1826pilipes Loew, 1873 (Sepsis), Lectotype now a synonym of Sepsis duplicata Haliday, 1838spectabilis Meijere, 1906 (Sepsis), Lectotype; syn. n. of Sepsis testacea Walker, 1856tuberculata Duda, 1926 (Sepsis), Lectotype now a synonym of Sepsis nitens Wiedemann, 1824acroleucoptera Duda, 1926 (Sepsis albopunctata var.), Lectotype now a synonym of Sepsis dissimilis Brunetti, 1910setipes Duda, 1926 (Sepsis arotrolabis var.), Lectotype now a synonym of Sepsis arotrolabis Duda, 1926subrecta Duda, 1926 (Sepsis femoriseta var.), Lectotype now a synonym of Sepsis femoriseta Duda, 1926aequipilosa Duda, 1926 (Sepsis lateralis var.), Lectotype now Sepsis aequipilosa Duda, 1926bigemmis Duda, 1926 (Sepsis lateralis var.), Lectotype now Sepsis bigemmis Duda, 1926validiseta Duda, 1926 (Sepsis macrochaetophora var.), Lectotype now Sepsis validisetakerteszi Duda, 1926 (Sepsis melanopoda var.), Lectotype now a synonym of Sepsis flavimana Meigen, 1826seticrus Duda, 1926 (Themira), Lectotypediscedens (Becker, 1903) (Toxopoda), Lectotype described as Amydrosoma discedens